"Are you able to access this website at all?" – team negotiations and macro-level challenges in telecollaboration. Issue 7 (2nd October 2016) - Fuchs, Carolin
ABSTRACT: This exploratory study contributes to the underexplored area of collaborative task formats in telecollaboration. The study investigates how English as a second language (ESL) student teachers in the US and English as a foreign language (EFL) student teachers in Turkey negotiated the design, implementation, and evaluation of technology-based English language learning tasks. The overall pedagogical goal of this spring 2014 project was to provide participants in different educational and institutional settings an opportunity to collaboratively explore and evaluate the affordances of technology tools in the design of joint learning tasks. This ethnographic case study triangulates questionnaires, telecollaboration logs, and computer-mediated communication data (blogs, emails) to examine the types of negotiation (personal, interactive, procedural) telecollaborative teams displayed at the project's micro levels (self, situated telecollaborative activity) and macro levels (institutional setting, political context). Findings indicate that one telecollaborative team, Global Team 2, effectively managed their learning as a group by making key decisions collectively about their work processes. The team's high number of procedural negotiation instances suggests a high degree of task-orientation, which may have aided their task completion. In contrast, the number of personal and interactive negotiation types was low. The latter, however, may have been called for midway through the project, when unexpected political developments in Turkey unfolded. Repercussions disturbed Turkish participants and affected social media, which were at the core of this telecollaboration. Implications focus on foregrounding personal and interactive negotiation via virtual Global Team check-ins, as well as on expanding collaborative tasks by incorporating perspectives on the wider institutional and sociopolitical contexts of participating institutions.